2018
DOI: 10.3390/app8091651
|View full text |Cite
|
Sign up to set email alerts
|

3D Printed Antibacterial Prostheses

Abstract: The purpose of the current investigation was two-fold: (i) to describe the development of 3D printed prostheses using antibacterial filaments and (ii) to verify the antibacterial properties of the 3D printed prostheses. Three-dimensional printed finger prostheses were manufactured using PLACTIVETM antibacterial 3D printing filaments. Two adults with left index finger amputations at the proximal phalanx were fitted with a customized 3D printed finger prosthesis manufactured with an antibacterial filament. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 25 publications
1
50
0
Order By: Relevance
“…However, several studies were conducted to investigate the insertion of drug molecules in the PPE during fabrication to offer an antimicrobial and antiviral protection. [31][32][33][34] A non-exhaustive list of open-source medical devices for COVID-19 is given in Table 2. The link to download the STL files is also given.…”
Section: Face Shieldsmentioning
confidence: 99%
“…However, several studies were conducted to investigate the insertion of drug molecules in the PPE during fabrication to offer an antimicrobial and antiviral protection. [31][32][33][34] A non-exhaustive list of open-source medical devices for COVID-19 is given in Table 2. The link to download the STL files is also given.…”
Section: Face Shieldsmentioning
confidence: 99%
“…The original and any follow-up scans or digital modifications can be preserved, providing a permanent record of a patient's limb [11,25]. In addition, it allows the use of a variety of materials for socket manufacturing, including antibacterial skin-safe filaments [48]. Despite such potential, 3D printing has been used primarily for grasping devices [20].…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments and applications in biomechanics introduced the utilization of a three-dimensional (3D) printing system to enhance the process of socket design. As reported by Zuniga [3], 3D printers have been utilized to develop prosthetic devices using antibacterial filaments. The investigation found that the 3D printer is capable of developing effective antibacterial finger prosthesis.…”
Section: Introductionmentioning
confidence: 99%
“…According to Nguyen et al [4], the design and 3D printing of the transfemoral prosthetic socket required less time compared to conventional methods. However, the evaluation for 3D printing prefabrication has not been discussed in most of the previously published research studies [3,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%